New lessons on TDP‐43 from old N. furzeri killifish. Issue 1 (23rd December 2021) - Louka, Alexandra; Bagnoli, Sara; Rupert, Jakob; Esapa, Benjamin; Tartaglia, Gian Gaetano; Cellerino, Alessandro; Pastore, Annalisa; Terzibasi Tozzini, Eva
Abstract: Frontotemporal dementia and amyotrophic lateral sclerosis are fatal and incurable neurodegenerative diseases linked to the pathological aggregation of the TDP‐43 protein. This is an essential DNA/RNA‐ binding protein involved in transcription regulation, pre‐RNA processing, and RNA transport. Having suitable animal models to study the mechanisms of TDP‐43 aggregation is crucial to develop treatments against disease. We have previously demonstrated that the killifish Nothobranchius furzeri offers the advantage of being the shortest‐lived vertebrate with a clear aging phenotype. Here, we show that the two N. furzeri paralogs of TDP‐43 share high sequence homology with the human protein and recapitulate its cellular and biophysical behavior. During aging, N. furzeri TDP‐43 spontaneously forms insoluble intracellular aggregates with amyloid characteristics and colocalizes with stress granules. Our results propose this organism as a valuable new model of TDP‐43‐related pathologies making it a powerful tool for the study of disease mechanism. Abstract : Our findings demonstrate that TDP‐43 from the fish N. furzeri associates with stress granules, acquires a doughnut‐like nuclear distribution and forms aggregates exclusively in old animals, mimicking what is observed in amyotrophic lateral schlerosis and other TDP‐43‐related diseases.